Iron-biofortification in rice by the introduction of three barley genes participated in mugineic acid biosynthesis with soybean ferritin gene - Masuda, Hiroshi; Kobayashi, Takanori; Ishimaru, Yasuhiro; Takahashi, Michiko; Aung, May S.; Nakanishi, Hiromi; Mori, Satoshi; Nishizawa, Naoko K. (Frontiers in Plant Science, 2013)
Iron deficiency is a serious problem around the world, especially in developing countries. The production of iron-biofortified rice will help ameliorate this problem. Previously, expression of the iron storage protein, ferritin, in rice using an endosperm-specific promoter resulted in a two-fold increase in iron concentration in the resultant transgenic seeds. However, further overexpression of ferritin did not produce an additional increase in the seed iron concentration, and symptoms of iron deficiency were noted in the leaves of the transgenic plants. In the present study, we aimed to further increase the iron concentration in rice seeds without increasing the sensitivity to iron deficiency by enhancing the uptake and transport of iron via a ferric iron chelator, mugineic acid. To this end, we introduced the soybean ferritin gene (SoyferH2) driven by two endosperm-specific promoters, along with the barley nicotianamine synthase gene (HvNAS1), two nicotianamine aminotransferase genes (HvNAAT-A and -B), and a mugineic acid synthase gene (IDS3) to enhance mugineic acid production in rice plants. A marker-free vector was utilized as a means of increasing public acceptance. Representative lines were selected from 102 transformants based on the iron concentration in polished seeds and ferritin accumulation in the seeds. These lines were grown in both commercially supplied soil (iron-sufficient conditions) and calcareous soil (iron-deficient conditions). Lines expressing both ferritin and mugineic acid biosynthetic genes showed signs of iron-deficiency tolerance in calcareous soil. The iron concentration in polished T3 seeds was increased by 4 and 2.5 times, as compared to that in non-transgenic lines grown in normal and calcareous soil, respectively. These results indicate that the concomitant introduction of the ferritin gene and mugineic acid biosynthetic genes effectively increased the seed iron level without causing iron sensitivity under iron-limited conditions.